Evaluasi dan Analisis Pelaksanaan Musyawarah Msyarakat Kelurahan Di Wilayah Puskesmas X Surabaya - Malida Nurul Hidayah (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2019)
Background: Ministry of Health Republic of Indonesia create a vision in health development that is "Independent and Justice of Healthy Community". The embodiment of the mission statement is poured in the form of a strategic programs which is District Alert programs through Village Community Deliberation and Community Self Survey. Purpose: The purpose of this study is to evaluate the implementation of Village Community Deliberation I and II of 2017 year in X Community Health Center. Methods: This type of research is descriptive observational. Data collection techniques used through interviews and secondary data collection. Methods of data analysis are done by doing a comparison between the data already obtained with the theory and guidelines in the implementation of research materials. This study lasted on February 26, 2018 - March 4, 2018. Results: Terms of implementers are still not in accordance with existing provisions, while for SMD executor already corresponding. In the aspect of the implementation of MMK and SMD is in accordance with the intended purpose as well as the results or output expected at the all stage. Conclusion: The stages of activities have held with appropriate the standards of existing regulations in Village Community Deliberation and Community Self Survey.